Pengaruh Dukungan Keluarga dan Goal Commitment terhadap Resiliensi pada Mahasiswa di Universitas Medan Area - Uswatun Hasanah; Abdul Murad; M. Abrar Parinduri (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
The focus of the problems in this study refers to the problems that occur in the lives of Medan Area University students ranging from physical, psychological, and sexual violence. Respondents of this study amounted to 150 people consisting of undergraduate and postgraduate students. The sampling technique used in this research is Quota Sampling. The age of this population ranges from 18-40 years. The measuring instrument in this study consisted of three instrumentals that had been modified by the researcher including the family support scale, goal commitment scale, and resilience scale. The calculation result for the Kolmogorov-Smirnov test is 0.200 which means the data is normally distributed. The results of the multiple regression test stated that there was a significant effect of family support and goal commitment on resilience in students at the University of Medan Area. For the partial regression test, it states that there is no significant effect of goal commitment on resilience in Medan Area University students. The results state that there is a significant effect of family support on resilience in Medan Area University students. The importance of the role of support that comes from family members as a positive reinforcement of behavior in the learning process so that learning methods can run optimally for students.